2010
DOI: 10.2169/internalmedicine.49.3093
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Adiponectin is Inversely Correlated with Metabolic Syndrome in Patients with Coronary Artery Disease

Abstract: Objective Hypoadiponectemia was observed to correlate with the prevalence or extent of coronary artery disease (CAD) r=0.267; p=0.008) but were negatively correlated with triglyceride concentration (TG; p=0.013). Multivariate forward stepwise linear regression analysis of the significant variables revealed that HDL-cholesterol concentration (R square=0.071, p=0.008) and age (R square=0.039, p=0.044)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Adiponectin is widely known to promote anti-inflammatory effects such as inhibition of NF-κB, TNF-α, IL-6 and IFN-γ, while increasing levels of IL-10 and IL1RA [16]. These effects are believed to confer protection against chronic disease conditions like atherosclerosis [17] and the metabolic syndrome [18]. To some extent, these protective effects are due to the ability of adiponectin to phosphorylate AMPK via ADRs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin is widely known to promote anti-inflammatory effects such as inhibition of NF-κB, TNF-α, IL-6 and IFN-γ, while increasing levels of IL-10 and IL1RA [16]. These effects are believed to confer protection against chronic disease conditions like atherosclerosis [17] and the metabolic syndrome [18]. To some extent, these protective effects are due to the ability of adiponectin to phosphorylate AMPK via ADRs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adiponectin strongly suppressed the proliferation and migration of vascular smooth muscle cells that is atherogenic [10,11]. In fact, it has been reported that higher adiponectin levels are closely associated with fewer MS components [12,13]. However, there have been a very limited number of clinical studies that examined the association between serum osteocalcin and MS in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, decreased plasma adiponectin levels have been demonstrated in patients with obesity, diabetes, and CHD [43][44][45] . Moreover, the degree of hypoadiponectinemia has been reported to be correlated with the degree of insulin resistance 46,47 , and hypoadiponectinemia has been shown to be closely associated with the clinical phenotype of metabolic syndrome 48,49 . Adiponectin served as an antiinflammatory molecule for vascular walls as well as adipose tissue 50 , hypoadiponectinemia was observed in obesity-linked diseases 43,51 .…”
Section: Table 4: Correlation Of Serum Adiponectin and Free Fatty Acimentioning
confidence: 99%